Pelatihan Pelaku Usaha Dalam Memanfaatkan Platform Shopee Untuk Pengembangan Produk Dan Peningkatan Jangkauan Pasar - Mohamad Nasirudin; Siti Nur Qomariyah; Yessita Puspaningrum; Adinda Tiara Choirunnisa; Maratus Sholihah; Mohamad Sahrul Putra Soleh; Rihlatil Hajjah; Syaviratul Mughoyaroh; Viona Ananda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
Training for business people in utilizing the Shopee platform aims to provide a deeper understanding and practical skills in managing business effectively in the digital era. This training is comprehensively designed, covering various important aspects needed to be successful on the platform. Starting from basic guides such as how to register and create an online shop, to effective digital marketing strategies, as well as product listing optimization techniques so that they appear more attractive and can compete in an increasingly competitive market. Apart from that, the training also focuses on sales data analysis, where participants are taught how to read and analyze data in depth. This understanding allows business actors to identify consumer purchasing patterns, so they can develop more accurate and targeted business strategies. Through an interactive learning approach and the use of real case studies, participants can learn from direct experience and apply their knowledge more practically in their own business context. The results of this training include the publication of a guidebook